A new species of Glabellula Bezzi, 1902 (Diptera: Mythicomyiidae: Glabellulinae) from Colombia, and an updated key to South American species - Ramos-Pastrana, Yardany; Córdoba-Suarez, Eric; Evenhuis, Neal. L (Zootaxa, 2023)
Glabellula Bezzi, 1902 has a cosmopolitan distribution and is a poorly studied group in the Neotropical Region, and completely unknown in Colombia. One new species of Glabellula is described from Colombia, namely Glabellula antioquensis sp. nov. (type-locality: Buriticá, La Angelina). Illustrations and a dichotomous key to the South American species are presented.